Artistic research, context research - Toledo Castellanos, Ricardo Benjamín (Universidad Pedagógica y Tecnológica de Colombia, 2012)
Some concepts in contemporary art works, dealing with some life aspects and passed through the sensitive and expressive test, are formulated in this paper and shed light on the foundation of researches about singular phenomenons of the existence. For this, it is argued that there are researches belonging to arts, fundamental researches that compromise the certainty of the assumptions where the sense system of a context has its bases (epoch, culture, nation, region). These researches come ahead of the researches of the rational-discursive enunciation fields, given that the last ones haven’t passed any protocol accepted yet by any community. To bring into play the certainty is done by a cognitive movement named by Martin Heidegger unconcealment [Unverborgenheit], and it consist on the interruption of the habituality of the beings who form the (trustworthy) family setting to put into perspective the fundamental structures that allow to produce its sense. The unconcealment, typical in art and in creative actions, sets up an event that stops the solidity of the established (social, ethical, technical, scientific, philosophical) order, and unleashes conditions for changing the lifestyles hold until then.